Use of Psychoeducation for Psychotic Disorder Patients Treated With Modern, Long-Acting, Injected Antipsychotics - Ventriglio, Antonio; Petito, Annamaria; Castaldelli-Maia, João Maurício; Torales, Julio; Sannicandro, Valeria; Milano, Eleonora; Iuso, Salvatore; Bellomo, Antonello (Frontiers in Psychiatry, 2021)
Introduction: There is an increased risk of adverse metabolic effects of some modern antipsychotic drugs, and concern that long-acting, injected preparations of them may increase such risk. We now report on clinical and metabolic outcomes in patient-subjects diagnosed with affective and non-affective psychotic disorders following exposure to psychoeducation on metabolic risks of modern antipsychotics followed by treatment with long-acting atypical injected antipsychotics over 6-months. Materials and Methods: 85 psychotic disorder outpatients (42 affective [AP]; 43 non-affective [NAP]) at the University of Foggia were treated with long-acting, injected, second-generation antipsychotics in association with a set of psychoeducational sessions concerning general health and potential effects of antipsychotic drug treatments. They were evaluated at baseline and six months. Results: Initially, NAP subjects reported higher ratings of positive and negative symptoms than AP subjects, were more likely to receive risperidone or paliperidone, with higher CPZ-eq doses of antipsychotics (294.0±77.8 vs. 229.3±95.8 mg/day), and shorter QTc electrocardiographic recovery intervals. During the 6-month follow-up, ratings of treatment-adherence improved through overall (+8.75%), and symptom-ratings decreased (–7.57%) as did Body-Mass Index (–2.40%; all p≤0.001). Moreover, serum levels of fasting glucose, hemoglobin glycosylation, cholesterol and prolactin concentrations all decreased, with little difference between subjects with AP vs. NAP. Discussion and Conclusions: A psychoeducational program was associated with consistent improvement in psychotic symptoms and several metabolic and physiological measures, as well as with treatment-adherence during six months of treatment with long-acting, injected, second-generation antipsychotics, in association with both affective and non-affective psychotic disorders.